2009
DOI: 10.1111/j.1471-6712.2008.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Family decision‐making in advanced dementia: narrative and ethics

Abstract: The families in these focus groups used the elders' life stories to frame their decisions for care. Providers working in primary care settings who work with families in making care decisions for cognitively impaired elderly patients may find narrative ethics more pertinent than principle-based ethics in understanding families' perspectives and priorities, while also recognizing their decision-making transition from using the principle of autonomy to that of beneficence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 41 publications
(37 reference statements)
4
108
0
4
Order By: Relevance
“…In their study 8 8 with 39 family members, Elliott et al 11 found that surrogates acquired decision making authority differently: in most cases, they assumed the role when a decision was unavoidable; others were explicitly designated as surrogates in advance; and some appointed themselves, but this was associated with decision making conflict.…”
Section: Acquisition Of Decision Making Rolementioning
confidence: 99%
See 1 more Smart Citation
“…In their study 8 8 with 39 family members, Elliott et al 11 found that surrogates acquired decision making authority differently: in most cases, they assumed the role when a decision was unavoidable; others were explicitly designated as surrogates in advance; and some appointed themselves, but this was associated with decision making conflict.…”
Section: Acquisition Of Decision Making Rolementioning
confidence: 99%
“…The decisions in which family surrogates are involved are diverse, ranging from lifestyle choices 9 , to medical decisions 10 , to specific stages such as end-of-life (EOL) care 11 . Numerous factors contribute to the complex nature of surrogate decision making; these include who makes the decisions, how this authority is delegated, and what sources of information are available to guide decision making 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Carers report a shift in the dynamic to a "mother/child" type relationship and Table 4. Summary of triggers, barriers, and facilitators to decision-making (Butcher et al, 2001;Ducharme et al, 2012) Desire to honor person with dementia's wishes (Elliott et al, 2009) Family and professionals perspectives (Livingston et al, 2010;Ducharme et al, 2012) Carer unable to cope and care/ deterioration in carer health (Cohen et al, 1993;Caron et al, 2006;Ducharme et al, 2012) Emotional impact (anguish, burden guilt) (Butcher et al, 2001;Livingston et al, 2010) Support from others once decision made (Butcher et al, 2001) Change in living environment (Caron et al, 2006) Resistance from person with dementia (Livingston et al, 2010;Chrisp et al, 2012;Wolfs et al, 2012;Chrisp et al, 2013) Relationship to person with dementia (Wackerbarth, 1999) Person with dementia's ability to make decisions (Caron et al, 2006) Barriers to accessing services/lack of support/information (Wackerbarth, 1999;Butcher et al, 2001;Livingston et al, 2010) Adapting caring role following a decision (Kwon and Tae, 2012) Cultural treachery and distress (Chang and Schneider, 2010;Chang et al, 2011;Kwon and Tae, 2012) Collaborating with healthcare professionals (Walker and Dewar, 2001;Heinrich et al, 2003;Torke et al, 2013) Role change to "mother/child" (Cairns, 2012) Mild to moderate dementia severity (Smebye et al, 2012) Knowing when the "right" take to ...…”
Section: Role Transitions and Perceptionsmentioning
confidence: 99%
“…However, the decision was carried through even though the person with dementia explicitly objected. Four studies (Golden, 2010;Elliott et al, 2009;Weber and Bailey, 2005;Forbes et al, 2012;Aminzadeh et al, 2009) present examples of how people with dementia are deceived into entering residential care and day care by being told that they are moving, or going somewhere else. Participating caregivers in Weber's and Bailey's (2005) focus groups refer to this phenomena as "therapeutic fibbing", which includes "…telling the patient that the move was temporary, stating that the patient was going to a resort or school, or telling the individual being placed that they were going there for medical tests or other health-related activities" (p. 28).…”
Section: Excludedmentioning
confidence: 99%